Using a Scenario‐Neutral Framework to Avoid Potential Maladaptation to Future Flood Risk. Issue 2 (7th February 2019) - Broderick, Ciaran; Murphy, Conor; Wilby, Robert L.; Matthews, Tom; Prudhomme, Christel; Adamson, Mark
Abstract: This study develops a coherent framework to detect those catchment types associated with a high risk of maladaptation to future flood risk. Using the "scenario‐neutral" approach to impact assessment the sensitivity of Irish catchments to fluvial flooding is examined in the context of national climate change allowances. A predefined sensitivity domain is used to quantify flood responses to +2 °C mean annual temperature with incremental changes in the seasonality and mean of the annual precipitation cycle. The magnitude of the 20‐year flood is simulated at each increment using two rainfall‐runoff models (GR4J, NAM), then concatenated as response surfaces for 35 sample catchments. A typology of catchment sensitivity is developed using clustering and discriminant analysis of physical attributes. The same attributes are used to classify 215 ungauged/data‐sparse catchments. To address possible redundancies, the exposure of different catchment types to projected climate is established using an objectively selected subset of the Coupled Model Intercomparison Project Phase 5 ensemble. Hydrological model uncertainty is shown to significantly influence sensitivity and have a greater effect than ensemble bias. A national flood risk allowance of 20%, considering all 215 catchments is shown to afford protection against ~48% to 98% of the uncertainty in the Coupled Model Intercomparison Project Phase 5 subset (Representative Concentration Pathway 8.5; 2070–2099), irrespective of hydrological model and catchment type. However, results indicate that assuming a standard national or regional allowance could lead to local over/under adaptation. Herein, catchments with relatively less storage are sensitive to seasonal amplification in the annual cycle of precipitation and warrant special attention. Plain Language Summary: Climate change presents a significant challenge for flood managers. Their decisions regarding the designation of vulnerable areas and investment in large‐scale flood prevention and relief schemes have long‐term implications for the attendant risk to human life and infrastructure. In some jurisdictions authorities have proposed a universal allowance on existing design measures that would offer protection against a set (e.g., 20%) increase in flood magnitude. However, this "one size fits all" approach ignores that river catchments have very different physical attributes that affect their sensitivity to change. We develop a framework that groups catchments based on their physical characteristics into distinct sensitivity types. The method follows the "scenario‐neutral" approach to impact assessment. Here two‐dimensional response surfaces showing flood sensitivity to incremental changes in rainfall and temperature are used in conjunction with the latest climate projections to tailor climate plans for individual catchments. The response surfaces are a valuable tool for identifying critical thresholds when proposed allowances fail to accommodate projected flood risk. For managers this helps to allocate resources where risk is greatest and balance the costs of increased protection against climate uncertainty. The study is conducted using 215 Irish catchments; however, we highlight its potential to aid adaptation efforts globally. Key Points: The "scenario‐neutral" framework provides valuable insights into the climate sensitivity of individual and regionalized catchment types Assuming a national allowance when factoring climate change into designs could lead to local over/under adaptation to future flood risk Catchments with relatively less storage capacity are more sensitive to an amplified seasonal precipitation cycle